Rancang Bangun Sistem Informasi Penerimaan Retribusi Berbasis Web Di Dinas Perhubungan Kota Palembang - Evni Hidayat (Teknik Komputer Politeknik Negeri Sriwijaya, 2022)
Through the Design and Build of a Web-Based Retribution Receipt Information System, it is able to provide a controlled and well-managed system by the Palembang City Transportation Service, especially in the south parking zone and north parking zone. The purpose of this study was to identify and identify the Retribution Receipt at the points of the web-based south parking zone and north parking zone at the transportation service of Palembang City. The system development method that will be used in this research is Waterfall, with a systematic approach, starting from the system requirements stage and then heading to the analysis, design, coding, testing/verification, and maintenance stages. This research can help the Department of Transportation in receiving retribution and help manage financial reports effectively and with the application or Web-Based Retribution Receipt Information System at the Palembang City Transportation Office, it can assist the agency in overcoming problems that occurred previously and increase effectiveness in managing financial statements.